PARTICIPATION OF LEADERS, COMMUNITY LEADERS AND PEOPLE IN FLOOD MANAGEMENT IN RANONG MUNICIPALITY, RANONG PROVINCE - Pantip Chuaynaket; Worawit Chindapol; Pawit Chalermwat (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The objectives of this research were to: 1) study the level of participation in flood management of leaders, community leaders, and people in Ranong municipality, Ranong province, and 2) compare the roles, participation, management, community leaders and people in flood management of the people in Ranong municipality, Ranong province. This was quantitative research using questionnaires. The research samples were 5 administrators, 15 community leaders selected by purposive sampling technique, and 17,904 people in Ranong municipality with 355 samples using Stratified Random Sampling (Krejcie and Morgan, 1970, pp. 608-609). The sample size was selected by simple random sampling. The research tool was a questionnaire. Data were analyzed by frequency, percentage, average, standard deviation, and Using the test ANOVA (One-Way ANOVA). The research results were as follows: 1) level of flood management in Ranong municipality, Ranong province in overall and in each aspect were at a high level, with average scores from high to low, namely participation in operations, participation in receiving benefits, participation in decision making, and participation in the assessments, respectively, and 2) the different roles and responsibilities of flood management affected flood management in terms of participation per decision, participation in operations, participation in receiving benefits and participation in the overall evaluation were different.